2024
DOI: 10.1039/d3em00369h
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene microplastics interaction and influence on the growth kinetics and metabolism of tilapia gut probiotic Bacillus tropicus ACS1

Pazhamthavalathil Anil Athulya,
Natarajan Chandrasekaran,
John Thomas

Abstract: Polystyrene microplastics affects the growth kinetics and cell viability of Bacillus tropicus ACS1, a probiotic isolated from tilapia gut. It induced oxidative stress and influenced the EPS production of the bacteria under in vitro conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that NPs can impact the activity of beneficial probiotic bacteria and may imbalance the biosynthesis of exopolysaccharides, initiating shifts within certain predominant microbial clusters. 9 Due to their extremely small size, NPs are more likely to cross the cell membrane barrier and enter the cell, which may cause more serious cellular level damages. 10 At the same time, NPs may adhere to other pollutants to aggravate the toxic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that NPs can impact the activity of beneficial probiotic bacteria and may imbalance the biosynthesis of exopolysaccharides, initiating shifts within certain predominant microbial clusters. 9 Due to their extremely small size, NPs are more likely to cross the cell membrane barrier and enter the cell, which may cause more serious cellular level damages. 10 At the same time, NPs may adhere to other pollutants to aggravate the toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…NP exposure can alter the prevalence of predominant microbial taxa in the guts of aquatic life. Studies have shown that NPs can impact the activity of beneficial probiotic bacteria and may imbalance the biosynthesis of exopolysaccharides, initiating shifts within certain predominant microbial clusters . Due to their extremely small size, NPs are more likely to cross the cell membrane barrier and enter the cell, which may cause more serious cellular level damages .…”
Section: Introductionmentioning
confidence: 99%